Rural Education adapting pedagogical methods: proposal for Youngsters and Adults Education without evasion in the quilombolas communities - Ieda Ribeiro Rodrigues; Haroldo de Vasconcelos Bentes (Universidade Federal do Norte do Tocantins, 2018)
This article proposes the inclusion of pedagogical procedures that value the local culture in the EJA classes of two schools of quilombola communities. The objective of this method is the regular participation of the student in the school, thus proposing the reduction in the school dropout rate through the modification of classroom teaching. We present reports of students and teachers where the problem of avoidance is justified. It is suggested differentiated dynamics exemplified in the discipline of Philosophy of Education with one of the classes of the Rural Education (UFPA). In the theoretical field it is defended a teaching that prioritizes the specificities of the subjects of the Youngsters and Adult Education (YAE) and the local culture. Contextualizing with Haroldo Bentes (2010, 2016), Caldart (2000; 2012) and National Curricular Guidelines for Elementary Education, Countryside Schools and Quilombola Education. Within the methodological foundations it is approached the integration of pedagogical methods adapted according to the local culture. It discusses the interaction and interest of the student of the YAE with the disciplines. It was at the end that the exchange of teacher-student knowledge stimulates socio-educational growth. Encouraging the student to stay in school and reducing the level of school dropout.